(3NQjOI GdYLGFH haQjOI GdZQGFHs - (3YeQ Hf eXaQ Hf YeQ H eMeO GHf CHj GdahGQS, CHh MaU, Rjf GdOjf GHf GdhQOj GdeYQj GdcfOj,J (B749 (3g` s
(3ChdgG (B:s
(3GdMeO ddg ZGaQ GdPfH hbGHd GdJhH TOjO GdYbGH CeG HYO , aEf NGdb GdNdb hGdHQjI hef dg GdEQGOI hGdeTjFI bO ejR Gdedhc hGdQYGI Yef HYVge ef GdQYjI s
(3BNQgG (B:s
(3hCcdgG OGFe dGTF efbWY cOGQ CMGOjKgG HCWjH GdNHQ ajgG ef GdNHQ eGde jLRfi Mdd hde jcf eOQckG HGdSeY hGdHUQ CHjGJgG SHY YTQ HYOgG eGjI cdGegG hYXI CHgG ef GdOQQ GdcJGH HMeO Gddg hYhfg hSMf Jhajbg hcQeg hGdMeO ddg hMOg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B701s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdLZQGajG h GdHdOGfs